Effects of fumaric acid supplementation on methane production and rumen fermentation in goats fed diets varying in forage and concentrate particle size - Zongjun Li; Nannan Liu; Yangchun Cao; Chunjia Jin; Fei Li; Chuanjiang Cai; Junhu Yao (Journal of Animal Science and Biotechnology, 2018)
Abstract Background In rumen fermentation, fumaric acid (FA) could competitively utilize hydrogen with methanogenesis to enhance propionate production and suppress methane emission, but both effects were diet-dependent. This study aimed to explore the effects of FA supplementation on methanogenesis and rumen fermentation in goats fed diets varying in forage and concentrate particle size. Methods Four rumen-cannulated goats were used in a 4 × 4 Latin square design with a 2 × 2 factorial arrangement of treatments: low or high ratio of forage particle size: concentrate particle size (Fps:Cps), without or with FA supplementation (24 g/d). Fps:Cps was higher in the diet with chopped alfalfa hay plus ground corn than in that with ground alfalfa hay plus crushed corn. Results Both increasing dietary Fps:Cps and FA supplementation shifted ruminal volatile fatty acid (VFA) patterns toward more propionate and less acetate in goats. An interaction between dietary Fps:Cps and FA supplementation was observed for the ratio of acetate to propionate (A:P), which was more predominant when FA was supplemented in the low-Fps:Cps diet. Methane production was reduced by FA, and the reduction was larger in the low-Fps:Cps diet (31.72%) than in the high-Fps:Cps diet (17.91%). Fumaric acid decreased ruminal total VFA concentration and increased ruminal pH. No difference was found in ruminal DM degradation of concentrate or alfalfa hay by dietary Fps:Cps or FA. Goats presented a lower ruminal methanogen abundance with FA supplementation and a higher B. fibrisolvens abundance with high dietary Fps:Cps. Conclusions Adjusting dietary Fps:Cps is an alternative dietary model for studying diet-dependent effects without changing dietary chemical composition. Fumaric acid supplementation in the low-Fps:Cps diet showed greater responses in methane mitigation and propionate increase.